JC viral loads in patients with Crohn's disease treated with immunosuppression: can we screen for elevated risk of progressive multifocal leukoencephalopathy?. Issue 10 (24th April 2008) - Verbeeck, J; Van Assche, G; Ryding, J; Wollants, E; Rans, K; Vermeire, S; Pourkarim, M R; Noman, M; Dillner, J; Van Ranst, M; Rutgeerts, P
Abstract : Background and aims: Anti-α4 integrin therapy with natalizumab is efficacious in refractory Crohn's disease and in multiple sclerosis, but carries an estimated 1/1000 risk of progressive multifocal leukoencephalopathy (PML) caused by reactivation of latent JC virus infection. Athough anti-α4 integrin therapies are likely to be introduced in the clinic, screening for the risk of PML has not been developed. Methods: We prospectively collected urine, serum, plasma and buffy coats from 125 patients with Crohn's disease, 100 control subjects with gastrointestinal (GI) disease, and 106 healthy volunteers. Four to eight weeks after this first sample collection, we additionally collected a set of urine, serum, plasma and buffy coat samples from the 125 patients with Crohn's disease, and a next set of samples was collected 12–16 weeks after the first collection. JC viral loads were determined with quantitative real-time polymerase chain reaction (PCR), and JC virus seroprevalence with a specific enzyme-linked immunosorbant assay (ELISA). Results: The overall JC virus seroprevalence was 65%. JC virus DNA copies were detected in the urine from 29–44% of subjects, both those with Crohn's disease and controls. Median viral loads were significantly higher in patients with Crohn's disease who were immunosuppressed (7.36×10 6 copies/ml) compared to healthy volunteers (2.77×10 5 copies/ml) and compared to GI controls (1.8×10 6 copies/ml). Clearance at any time point occurred in 4/107 (3.7%) subjects only. JC viraemia was found in two patients with Crohn's disease. Conclusions: The natural history of JC virus in patients with Crohn's disease is still unknown. Our study results show that JC virus latency and urine viral shedding is frequent in immunosuppressed patients with Crohn's disease. More prospective studies are needed in order to agree on possible recommendations concerning the exclusion of patients with JCV viraemia from anti-α4 integrin treatment.